Damping measurements from microseismic signals to infer rock mass damaging - D’Angiò, Danilo; Lenti, Luca; Martino, Salvatore (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="{"1":2,"2":"Geophysical monitoring performed on unstable portions of rock masses can help in defining a variation in its stability conditions, resulting as a useful indicator for landslide risk reduction. In particular, understanding geophysical markers of rock mass damaging, intended as the processes that lead to the formation or to the growth of fractures, could improve risk mitigation strategies. This work illustrates a methodology used\rto process a microseismic dataset acquired on a 12 m3 rock block prone to failure, located in the Acuto quarry test site, Central Italy. The microseismic monitoring campaign lasted 3 months and was conducted by deploying 6 one-component accelerometers partially on the rock block and partly on the rock mass wall. The acquisition was set in continuous mode and with a sampling frequency of 2400 Hz, allowing to collect hundreds of microseismic events. The damping coefficient of each event has been evaluated for some frequencies of interest, then the values have been averaged and compared through the whole period analysed in order to derive possible variations in the vibrational behavior of the monitored rock block. Despite no relevant changes have been noted, this technique could be helpful for analysing bigger datasets or to study different sites in which the external stresses are more intense and recurrent."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Geophysical monitoring performed on unstable portions of rock masses can help in defining a variation in its stability conditions, resulting as a useful indicator for landslide risk reduction. In particular, understanding geophysical markers of rock mass damaging, intended as the processes that lead to the formation or to the growth of fractures, could improve risk mitigation strategies. This work illustrates a methodology used to process a microseismic dataset acquired on a 12 m3 rock block prone to failure, located in the Acuto quarry test site, Central Italy. The microseismic monitoring campaign lasted 3 months and was conducted by deploying 6 one-component accelerometers partially on the rock block and partly on the rock mass wall. The acquisition was set in continuous mode and with a sampling frequency of 2400 Hz, allowing to collect hundreds of microseismic events. The damping coefficient of each event has been evaluated for some frequencies of interest, then the values have been averaged and compared through the whole period analysed in order to derive possible variations in the vibrational behavior of the monitored rock block. Despite no relevant changes have been noted, this technique could be helpful for analysing bigger datasets or to study different sites in which the external stresses are more intense and recurrent.